APPLICATION OF THE PROBLEM BASED-FISHBONE MODEL ON REPRODUCTIVE SYSTEM MATERIAL IN SMA N 1 DEMPET - Subekti, Arum; WH, Nugrahaningsih; ., Lisdiana (FMIPA UNNES, 2019)
Students achievement that are less than optimal indicate the students thinking skills are not maximal. To improve students thinking skills can be done in several ways among others, students further deepen  the concept of material, to provide further explanation and to provide alternative solutions to problems, so that students in the future are expected to solve problems in the environment. One learning model that can improve students thinking skills is problem based learning. Problem-based  learning models can encourage students ability to conduct investigations and be able to provide alternative solutions to problems. This study aims to analyze the model problem based -fishbone on reproductive system material influencing learning outcomes and the health care attitude of high school students. This study used a quasi experimental design with  pretest-posttest control group design. The sample of this study was students of class XI MIPA 2 and XI MIPA 6 in SMA N 1 Dempet which were determined using purposive sampling technique. The independent variable is a model problem based-fishbone on reproductive system material. Dependent variables are student learning outcomes and student health care attitudes. How to retrieve data using test and observation sheet questions. The results of data analysis showed that student learning outcomes could increase after learning activities were completed with completeness for both classes in a row 79.54% and 90.48%, and students had good health care attitudes. Based on the results of the study it can be concluded that the application of the model problem based- fishbone influences learning outcomes and health care attitudes in high school students.